Pengembangan Modul Pembelajaran berbasis Inkuiri pada Materi Pernikahan Mata Pembelajaran PAI dan Budi Pekerti Kelas XII di SMAN 1 Pariangan Kabupaten Tanah Datar - Jamal Mirdad; Afriwes Afriwes; Muhammad Amin (Journal on Education, 2023)
The purpose of the study is to obtain data on whether the characteristics of the resulting learning module have met valid and practical criteria. The type of research used is development research, which is a research method used to produce products / modify products, namely inquiry-based learning modules. The development model used is the 4-D model, namely: define, design, develop, and dissemination and is only carried out until the develop stage. Data collection techniques are carried out through questionnaires, observations and interviews. Based on research that has been done, it is known that the inquiry-based learning module on the marriage material that has been produced is very valid by showing the calculated value of the Aiken index coefficient of 82 through validation tests by 3 validators. The results of the practicality test through the student response questionnaire are categorized as very practical with an assessment percentage of 92.08%.